The clash of cultures in Ethiopia: Retro- & perspective - Joanna Mantel-Niećko (Studies in African Languages and Cultures, 1995)
This paper deals with the “world” as seen by various states on the continents surrounding the basin of the Mediterranean Sea at various times. For the powers in that area, a constant strategic point was among others the Horn of Africa, and in it Ethiopia. As we watch the crossing of the great cultural currents around the Mediterranean Sea with the civilization of Ethiopia, we note that those encounters are in fact collisions. They are not historically continuous processes like those which can be observed on the European plains.